STUDENTS’ PERSPECTIVES OF ONLINE ENGLISH LEARNING APPLICATIONS USE IN ENHANCING THEIR SPEAKING ABILITY AT SYSTEM INFORMATION DEPARTMENT - Rina Irawan Nasution; Syafrida Hafni; Editha Dewi Purnamasari; Saimarlina Harahap; Musthafa Haris Munandar (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
One of the factors that influenced in language learning was digital or online applications use. Nowdays, students are commonly use their devices to enhance their language ability, especially in speaking ability. This research was conducted at English class of System Information Department students, Institute of Science and Technology of Padang Lawas Utara. First semester of System Information Department students were the respondents of this research. The survey investigated the following aspects, namely: preferences, actual use, ease of use, experience, and learning opportunities. Moreover, this research also investigated the students to share their positive and negative benefits of online English applications use in the classroom. There were 52 students completed the survey. The results showed that most of students viewed positively responding to the potential utilization and integration of online English applications use. However, there are some students expressed that the use of online English applications in language learning, especially to enhance their speaking ability did not give an efficient or effective method and did not get significant effect on their speaking ability in language learning class.